Influence of prior experiences on pre-service language teachers' perception of teaching - Yuksel, H. Gulru; Kavanoz, Suzan (ELSEVIER SCIENCE BV, 2015)
Extended prior experience causes student teachers to develop personal beliefs and knowledge about teaching. Through their teacher education, they are enculturated into the profession. This process may sometimes create a tension between old and new schemes due to different factors such as prior experience and predispositions about teaching. For a better understanding of their professional and personal formation as teachers investigating pre-service teachers' biographical background experiences and the aspects of teaching they find important is essential. This study aims at exploring positive and negative influences of pre-service teachers' previous experiences, the aspects of teaching they find the most and least appealing and their expectations from the teacher education program. The study is qualitative in nature. Data was collected from a total of twenty six senior pre-service teachers enrolled in English Language Teaching Program at a state university in Turkey through semi-structured interviews and written comments. Qualitative content analysis was adopted to analyze the responses. While the pre-service teachers reported to be positively influenced by the teachers with pedagogical content knowledge, they are negatively influenced by the teachers who lack content and pedagogical knowledge. Among the motivating aspects of teaching, intrinsic career value, personal utility value and social utility value were the most frequently mentioned motivating aspects. Their concerns were related to task perception, most of which were connected to task demand issues. The most frequently mentioned expectation was the improvement in pedagogical knowledge. (C) 2015 Published by Elsevier Ltd.
Keywords: concern; expectation; EPOSTL; motivation; teacher education; STUDENT-TEACHERS; MOTIVATIONS; HISTORIES; BELIEFS; LIFE; Education & Educational Research; Social Sciences - Other Topics